Visual detection of formaldehyde by highly selective fluorophore labeling via gold(iii) complex-mediated three-component coupling reaction. Issue 27 (12th June 2015) - Wong, Kong-Fan; Deng, Jie-Ren; Wei, Xiao-Qun; Shao, Shi-Ping; Xiang, Da-Peng; Wong, Man-Kin
Abstract : Visual fluorescence detection of formaldehyde by a highly selective gold(iii ) complex-mediated three component coupling reaction has been described. Abstract : A novel method for visual detection of formaldehyde with excellent selectivity via a gold(iii ) complex-mediated three-component coupling reaction of resin-linked sterically bulky amines and fluorescent alkynes has been developed.